2022
DOI: 10.1096/fj.202101577rr
|View full text |Cite
|
Sign up to set email alerts
|

The interdependent relationship between the nitric oxide signaling pathway and primary cilia in pulse electromagnetic field‐stimulated osteoblastic differentiation

Abstract: Pulsed electromagnetic fields (PEMFs) have long been recognized being safe and effective in treating bone fracture nonunion and osteoporosis. However, the mechanism of osteogenic action of PEMFs is still unclear. While primary cilia are reported to be a sensory organelle for PEMFs, and nitric oxide (NO) plays How to cite this article: He W-F, Qin R, Gao Y-H, et al. The interdependent relationship between the nitric oxide signaling pathway and primary cilia in pulse electromagnetic field-stimulated osteoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We have previously reported that the existence of primary cilia is the precondition for the normal expression of BMP receptor‐II, soluble adenylyl cyclases, Wnt10b, or the ciliary components of the nitric oxide signaling pathway (He et al, 2022; Shi et al, 2017; Xie et al, 2016; Zhou et al, 2019). It was the first time that shortening/absorption of primary cilia was found to increase the expression level of TRPV4, which was located in primary cilia and expressed at a relative low level in normal condition.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the existence of primary cilia is the precondition for the normal expression of BMP receptor‐II, soluble adenylyl cyclases, Wnt10b, or the ciliary components of the nitric oxide signaling pathway (He et al, 2022; Shi et al, 2017; Xie et al, 2016; Zhou et al, 2019). It was the first time that shortening/absorption of primary cilia was found to increase the expression level of TRPV4, which was located in primary cilia and expressed at a relative low level in normal condition.…”
Section: Discussionmentioning
confidence: 99%
“…Immobile cilia are also commonly referred to as primary cilia; they sense changes in the microenvironment surrounding the cell and mediate a variety of important signal transductions within the cell [ 34 , 35 , 36 ]. Wen-Fang He et al revealed that PEMFs promote osteogenic differentiation through nitric oxide signaling within primary cilia, thus inhibiting osteoporosis progression [ 37 ]. According to Yan-Fang Xie et al, PEMFs stimulated osteoblast differentiation and mineralization in a primary cilia-dependent manner and inhibited osteoporosis progression [ 38 ].…”
Section: Pemfs For Osteoporosismentioning
confidence: 99%
“…It has been shown that primary cilia act as sensory organs involved in pulsed electromagnetic field-mediated bone formation ( 32 ). He ( 33 ) found that PEMF stimulates osteogenic differentiation mainly by activating the NOS/NO/sGC/cGMP/PKG signaling pathway and thus stimulating osteogenic differentiation, and it is noteworthy that all components of this signaling pathway, including iNOS, eNOS, sGC, PKG-1, and PKG-2 are localized in the primary cilia, and that eNOS needs to be phosphorylated within the primary cilia in order to be phosphorylated. As well as Liu ( 25 ) also reported that the primary cilia of osteoblasts in rats exposed to microgravity rapidly became shorter or even disappeared, and this phenomenon was accompanied by a significant reduction in osteogenic differentiation and mineralization of osteoblasts.…”
Section: The Role Of Primary Cilia In Bone Metabolismmentioning
confidence: 99%